Effects of goal orientation and task complexity on audit judgment performance / Zuraidah Mohd Sanusi, Takiah Mohd Iskandar and June M. L. Poon - Mohd Sanusi, Zuraidah; Mohd Iskandar, Takiah; M. L. Poon, June (Accounting Research Institute (ARI) & Faculty of Accountancy, 2007)
This study examined the predictive effects of goal orientation and task complexity on audit judgment performance. We hypothesized that (a) learning goal orientation would relate positively with audit judgment performance, (b) performance-avoidance goal orientation and task complexity would relate negatively with audit judgment performance, and (c) performance-approach goal orientation would interact with task complexity to predict audit judgment performance.